Inhibition of proteolysis protects hippocampal neurons from ischemia. - Lee, K S (1991)
Intense proteolysis of cytoskeletal proteins occurs in brain within minutes of transient ischemia, possibly because of the activation of calcium-sensitive proteases (calpains). This proteolytic event precedes overt signs of neuronal degeneration, is most pronounced in regions of selective neuronal vulnerability, and could have significant consequences for the integrity of cellular function. The present studies demonstrate that (i) the early phase of enhanced proteolysis is a direct response to hypoxia rather than other actions of ischemia, (ii) it is possible to pharmacologically inhibit the in vivo proteolytic response to ischemia, (iii) inhibition of proteolysis is associated with a marked reduction in the extent of neuronal death, and (iv) protected neurons exhibit normal-appearing electrophysiological responses and retain their capacity for expressing long-term potentiation, a form of physiological plasticity thought to be involved in memory function. These observations indicate that calcium-activated proteolysis is an important component of the post-ischemic neurodegenerative response and that targeting this response may be a viable therapeutic strategy for preserving both the structure and function of vulnerable neurons.